Simulation for teaching cardiorespiratory resuscitation by teams: setting and performance assessment - Emílio Carlos Alves dos Santos; Cor Jesus Fernandes Fontes; Eloana Ferreira D’Artibale; Jocilene de Carvalho Miravete; Gimerson Erick Ferreira; Mara Regina Rosa Ribeiro (Revista Latino-Americana de Enfermagem, 2021)
Abstract Objective: to evaluate the acquisition of cognitive knowledge in cardiorespiratory resuscitation through training mediated by health simulation and to verify satisfaction with the teaching methodology design. Method: a study of quasi-experimental intervention, of the before and after type, with only one group. Population composed of medical students in the internship phase, nurses and resident physicians, nursing technicians and nurses of the institution’s effective staff. Convenience sampling consisting of 91 participants. Data collected through the Sociodemographic and Educational Questionnaire, Knowledge Test and Simulation Design Scale. Data was organized in tables and analyzed based on absolute frequencies, measures of central tendency and dispersion, Cronbach’s alpha reliability test, Wilcoxon’s test. Results: the increase in cognitive learning was 81.9%, being that for nursing technicians it was 117.8 %. Wilcoxon’s test showed a significant increase (p<0.0001) in knowledge. The Simulation Design Scale, displayed 4.55 of global mean. Cronbach’s alpha pointed good internal consistency (0.898). Conclusion: the health simulation was effective as a learning-teaching method in cardiorespiratory resuscitation, being effective in increasing knowledge in cardiorespiratory arrest, with a great level of design satisfaction.